An investigation into the bioremediation of black olive brine wastewater - Werner, Craig Michael (Centre for Bioprocess Engineering Research, 2014)
In South Africa, the table olive industry is burgeoning and as a consequence, the large volume of fermentation wastewaters that are generated have created environmental concerns, as these wastewaters have the potential to pollute rivers and ground waters. Currently, these wastewaters are disposed of in large evaporation ponds, but this is not considered to be the optimal treatment solution, due to the potential for pollution and environmental damage. This thesis describes an investigation into the bioremediation of black olive fermentation wastewaters. Wastewaters, from both the table olive and olive oil industries, are toxic and this toxicity can be attributed to the phenolic compounds present. These compounds are known to have antimicrobial and phytotoxic effects. Aerobic biological treatments have been extensively investigated in order to reduce the phenolic fraction of olive mill wastewaters (OMW) with relative success. Biological treatment methods are also cheaper than chemical or physical treatment methods. Therefore, it was decided to investigate aerobic biodegradation of black olive fermentation wastewater (olive wastewater) from the production of black (Kalamata) olives.